Metabolic reprogramming of natural killer cells in obesity limits antitumor responses. (December 2018) - Michelet, Xavier; Dyck, Lydia; Hogan, Andrew; Loftus, Roisin; Duquette, Danielle; Wei, Kevin; Beyaz, Semir; Tavakkoli, Ali; Foley, Cathriona; Donnelly, Raymond; O'Farrelly, Cliona; Raverdeau, Mathilde; et al.
Abstract Up to 49% of certain types of cancer are attributed to obesity, and potential mechanisms include overproduction of hormones, adipokines, and insulin. Cytotoxic immune cells, including natural killer (NK) cells and CD8+ T cells, are important in tumor surveillance, but little is known about the impact of obesity on immunosurveillance. Here, we show that obesity induces robust peroxisome proliferator-activated receptor (PPAR)-driven lipid accumulation in NK cells, causing complete 'paralysis' of their cellular metabolism and trafficking. Fatty acid administration, and PPARα and PPARδ (PPARα/δ) agonists, mimicked obesity and inhibited mechanistic target of rapamycin (mTOR)-mediated glycolysis. This prevented trafficking of the cytotoxic machinery to the NK cell–tumor synapse. Inhibiting PPARα/δ or blocking the transport of lipids into mitochondria reversed NK cell metabolic paralysis and restored cytotoxicity. In vivo, NK cells had blunted antitumor responses and failed to reduce tumor growth in obesity. Our results demonstrate that the lipotoxic obese environment impairs immunosurveillance and suggest that metabolic reprogramming of NK cells may improve cancer outcomes in obesity. Obesity is a risk factor for cancer. Lynch and colleagues show that obesity alters the cellular metabolism of natural killer cells and decreases their antitumor surveillance and effector responses.